PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU DENGAN SIKAP PERUBAHAN SEBAGAI VARIABEL INTERVENING - Junaidi Siahaan; Mega Romauly Tampubolon (Politeknik Bisnis Indonesia, 2021)
Education is a human effort to develop human values. Education is the formation of human resources. Reliable human resources are moral, intelligent and skilled in order to have the potential to face local and global competition. The success achieved by the school in creating a comfortable and conducive environment is determined by several things, namely the role of the principal. The principal as managerial in this case acts as the head in managing the school and also the managerial ability of the principal will improve student achievement or learning outcomes. The quality of education can be seen based on the achievements of the students, this will affect the performance of teachers, while the performance of teachers is strongly influenced by the managerial ability of the principal. This study aims to determine the effect of the managerial ability of the principal of the Tanjung Morawa Methodist Private Elementary School on attitude change, to determine the effect of organizational climate on attitude change, to determine the effect of the principal's managerial ability to teacher performance, and to determine the effect of organizational climate on teacher performance. The data used in this study is primary data obtained by distributing questionnaires to teachers at the Tanjung Morawa Methodist Private Elementary School. The data analysis test was carried out using analysis techniques, namely Confirmatory Factor Analysis, Structural Equation Modeling. The research instrument testing used is validity test and reliability test, as well as suitability test and statistical test.